2015
DOI: 10.1016/j.gendis.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Sustained high level transgene expression in mammalian cells mediated by the optimized piggyBac transposon system

Abstract: Sustained, high level transgene expression in mammalian cells, especially stem cells, may be desired in many cases for studying gene functions. Traditionally, stable transgene expression has been accomplished by using retroviral or lentiviral vectors. However, such viral vector-mediated transgene expression is often at low levels and can be reduced over time due to low copy numbers and/or chromatin remodeling repression. The piggyBac transposon has emerged as a promising non-viral vector system for efficient g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 63 publications
0
51
0
1
Order By: Relevance
“…293pTP cells were derived from HEK-293 cells and overexpression of human Ad5 pTP gene as previously characterized [50]. The cell lines are maintained in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS, Gemini Bio-Products, West Sacramento, CA), containing 100 U/ml penicillin and 100 mg/ml streptomycin, at 37°C in 5% CO 2 as described [51-53]. Unless indicated otherwise, all other reagents were purchased from Sigma-Aldrich (St. Louis, MO) or Thermo-Fisher Scientific (Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…293pTP cells were derived from HEK-293 cells and overexpression of human Ad5 pTP gene as previously characterized [50]. The cell lines are maintained in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS, Gemini Bio-Products, West Sacramento, CA), containing 100 U/ml penicillin and 100 mg/ml streptomycin, at 37°C in 5% CO 2 as described [51-53]. Unless indicated otherwise, all other reagents were purchased from Sigma-Aldrich (St. Louis, MO) or Thermo-Fisher Scientific (Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…All experimental procedures were carried out in accordance with the approved guidelines. Briefly, HeyA8 stably labeled with firefly luciferase (HeyA8-FLuc) was constructed with piggybac system [37,43,66]. Exponentially growing HeyA8-FLuc cells were infected with AdR-siIGF1R or Ad-RGFP for 36h and collected, resuspended at 10 7 cells/ml and injected subcutaneously into the flanks of athymic nude mice (Harlan Laboratories, 6-8 week old, male, 10 6 cells per injection, and 4-6 sites per mouse).…”
Section: Xenograft Tumors and Xenogen Bioluminescence Imagingmentioning
confidence: 99%
“…We have recently optimized the piggyBac transposon system, which has been shown to have significant advantages over retroviral vectors in making stable lines with high levels of transgene expression [18, 21, 22]. Using the PBC2 as a base vector we subcloned six genes of human adenovirus type 5 (i.e., E1A, E1B19K, E1B55K, pTP, DBP, and DNA Pol) and the host factor OCT1 into this vector (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve a high level and stable transgene expression in 293 cells, we choose to use our optimized piggyBac transposon-based gene expression system [18, 21, 22], which can effectively integrate multiple copies of the transgene into relatively AT-rich regions of host chromosomes. We successfully established six types of genetically modified 293T M lines with different combinations of viral genes and/or OCT1 and found that the stable 293T M lines express high levels of transgenes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation